Perceptions of High School Principals in A Southeastern Urban School District on Leadership Practices and Parental Involvement - Graham, Elizabeth Chattmon (2007)
The purpose of this study was to examine the leadership practices of high school principals and parental involvement and to examine to what extent those practices differed between principals and how they related to parental involvement. The study revealed major issues surrounding parental involvement such as how principals defined parental involvement, how principals communicated the importance of parental involvement; what parental involvement activities impact student achievement; what common leadership practices influenced parental involvement; and what are some common experiences of high school principals regarding parental involvement. The methodology employed to conduct this qualitative study was face-to-face audio-taped interviews at the school site where each principal was in the lead role. Principals were asked protocol questions about their leadership practices which they previewed before the scheduled interview meeting. During the interview, principals responded to sub-topic questions which were of a more in-depth nature, to determine the extent to which they employed the practices they said they employed. The major findings of this study revealed several points about principals practices and parental involvement. One such finding was that high school principals 2 differ in their definitions of parental involvement. Another finding was that principals communicate the importance of parental involvement through their practices. Findings further indicated that few to no parental involvement activities have impacted student achievement; that few to no leadership practices influence parental involvement, and that the most common experience shared between high school principals regarding parental involvement is the challenge of strengthening parental involvement. The implications of this study are because principals are the leaders and tone-setters of the school, they must continue assessing their daily practices and become more creative in their practices aimed at stronger parental involvement, for as of yet, they have not discovered, through their present leadership practices, activities that elicit stronger parental involvement